2008
DOI: 10.1007/s11293-008-9138-6
|View full text |Cite
|
Sign up to set email alerts
|

Running the Numbers on Lotteries and the Poor: An Empirical Analysis of Transfer Payment Distribution and Subsequent Lottery Sales

Abstract: Lottery, Transfer payments, Liquidity constraints, Permanent income hypothesis, D00, D12, D91, H50, H53, I00, I38,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Second, using TDR as a proxy of financial and social burdens, this study found that TDR is positively related to demand, which is consistent with previous research that used transfer payment as a measure of financial and social burdens (Weinbach and Paul, 2008). This finding is consistent with the prediction of indivisibility in expenditure account, which suggested that under certain circumstances, people derive additional utility from risk seeking.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Second, using TDR as a proxy of financial and social burdens, this study found that TDR is positively related to demand, which is consistent with previous research that used transfer payment as a measure of financial and social burdens (Weinbach and Paul, 2008). This finding is consistent with the prediction of indivisibility in expenditure account, which suggested that under certain circumstances, people derive additional utility from risk seeking.…”
Section: Discussionsupporting
confidence: 89%
“…Weinbach and Paul (2008) investigation of the relationship between the amount of lottery tickets purchased across the United States and the distribution of government transfer payments also lend evidence to the interplay between consumption indivisibility and limited accessibility of credit market. Using weekly lottery sales data, they demonstrated an increase in lottery activity during weeks in which transfer payments are distributed.…”
Section: Consumer Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Financial burden: In line with the indivisibility in expenditure reasoning, financial burden is hypothesized to be positively correlated with the demand. Weinbach and Paul (2008) investigation of the relationship between the amount of lottery tickets purchased across the United States and the distribution of government transfer payments also lend evidence to the interplay between consumption indivisibility and limited accessibility of credit market. Using weekly lottery sales data, they demonstrated an increase in lottery activity during weeks in which transfer payments are distributed.…”
Section: Consumer Characteristicsmentioning
confidence: 97%
“…These works lead to the construction of effective price in estimating lottery demand (Gulley and Scott, 1993;Forrest et al, 2000). The indivisibility in consumption hypothesis and strategic labor supply (i.e., "something for nothing") hypothesis can be tested based on their specific predictions about the relationship between demand and certain socio-demographic variables, such as income, population age composition, and profession (Nyman et al, 2008;Weinbach and Paul, 2008). The gambling as consumption examined how the attractiveness of the game impact the demand (García and Rodríguez, 2007;Humphreys et al, 2013;Paul and Weinbach, 2013;Mao et al, 2014).…”
Section: Determinants Of Demand For Sports Lotterymentioning
confidence: 99%